Ekspresi dan Peran Siklooksigenase-2 dalam Berbagai Penyakit di Rongga Mulut - Rendra Chriestedy Prasetya (Fakultas Kedokteran Gigi Universitas Jember, 2015)
Cyclooxygenase-2 is part of the cyclooxygenase enzyme that plays a role in the inflammatory process has produce of prostaglandins (PG) such as PGE2. Prostaglandin E2 plays an important role in the pathogenesis of periodontal disease because it leads to increased vascular permeability, vasodilatory, edema. This review intends to give an overview the role of COX-2 in oral diseases likely periodontitis to be better understood and the future of our research that may facilitate the development of diagnosis and therapies. Cyclooxygenase is enzyme that plays of catalyze biosynthesis of prostaglandins and contained in two forms of COX-1 and COX-2. Cyclooxygenase-2 activity has increased in inflammation especially wound formation and periodontitis. In periodontitis, invasion of lipopolysacharide can Increase COX-2 activity in smooth blood muscle that can lead atherosclerosis. COX-2 inhibition can lead healing process that characterized fibroblast formation.it is concluded that the presence COX-2 in gingival tissue and gingival crevicular fluid can be used as biomarkers about the severity of periodontal disease, healing process and risk of atherosclerosis.